Renewable and Waste-Heat Utilisation Technologies: Thermal Energy Recovery, Conversion, Upgrading and Storage - Handagama,NB; White,MT; Sapin,P; Markides,CN (2023)
Understand the science and engineering behind conventional and renewable heat loss recovery techniques with this thorough reference. Provides you with the knowledge and tools necessary to assess the potential waste-heat recovery opportunities that exist within various industries and select the most suitable technology. In particular, technologies that convert waste heat into electricity, cooling or high-temperature heating are discussed in detail, alongside more conventional technologies that directly or indirectly recirculate heat back into the production process. Essential reading for professionals in chemical, manufacturing, mechanical and processing engineering who have an interest in energy conservation and waste heat recovery.